Ewolucja aktuarialnych modeli trwania życia i ich wpływ na rozwój ubezpieczeń na życie - ujęcie retrospektywne - Wycinka, Ewa (The Evolution of Actuarial Models and Their Influence on Life Insurance Development - Retrospective Approach, 2008)
Premiums and life reserves evaluation requires some assumptions concerning human life survival and the level of interest rate. These two factors are crucial for constructing adequate actuarial models. An actuarial model is a simplified mathematical view of the reality based on certain assumptions. Assumptions' adequacy plays an important role in model efficiency. The main purpose of this article is to present the evolution of actuarial models from Dodson (1755) to Lee-Carter (1992) and the influence of actuarial models development on life insurance evaluation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 499-507